Increased Cognitive Load Leads to Impaired Mobility Decisions in Seniors at Risk for Falls - Nagamatsu, Lindsay S. (2011)
Successful mobility requires appropriate decision-making. Seniors with reduced executive functioning— such as senior fallers—may be prone to poor mobility judgments, especially under dual-task conditions. We classified participants as “At-Risk” and “Not-At-Risk” for falls using a validated physiological falls-risk assessment. Dual-task performance was assessed in a virtual reality environment where participants crossed a simulated street by walking on a manual treadmill while listening to music or conversing on a phone. Those “At-Risk” experienced more collisions with oncoming cars and had longer crossing times in the Phone condition compared to controls. We conclude that poor mobility judgments during a dual-task leads to unsafe mobility for those at-risk for falls.